Parenting perspective on the psychosocial correlates of adolescent sexual and reproductive health behavior among high school adolescents in Ethiopia - Belete Yimer; Wassachew Ashebir (BMC, 2019)
Abstract Background While parents are a crucial part of the social environment in which adolescents live, learn and earn, they could play important roles in efforts to prevent adolescent sexual and reproductive health (SRH) risk behaviors and promote healthy development. Involving parents in prevention programs to risky SRH practices in adolescents requires understanding of the effect of different parenting practices and styles on these behaviors. The purpose of this study was to investigate the relationships between various aspects of perceived parenting and self-reported engagement in sexual risk behavior among adolescents. Methods A cross-sectional study was employed among 406 randomly selected 14-19 years old high school adolescents in Legehida district, Northeast Ethiopia from 15 February to 15 March/ 2016. Structured and pre-tested self-administered questionnaire adapted from the Youth Risk Behavior Surveillance questionnaire was used for the data collection. Bivariate and multivariate logistic regression analysis with odds ratio along with the confidence interval of 95% were used. P-value < 0.05 were considered for statistical significance. Results About two-third (64.5%) of the participants reported that they had ever had sex. Nearly half (48.6%) of the participants who were currently sexually active reported that they engaged in at least one type of risky sexual behavior. Specifically, 42.7% reported starting sexual life earlier, 32.2% having more sexual partners in the past 12 months and 23.8% never used condom during the most recent sexual intercourse. High quality parent─adolescent relationships (AOR = 0.53; 95% CI (0.45-0.63) and authoritative form of parenting (AOR = 0.74; 95% CI (0.61-0.92) were associated with lower odds of engaging in risky sexual behaviors in adolescents. The odds of risky sexual behaviors were about three-fold higher in adolescents who perceived parental knowledge as poor (AOR = 2.97; 95% CI (1.51-4.25) and to some extent (AOR = 3.00; 95% CI (1.43-5.55) toward SRH than those whose parents were very knowledgeable. Adolescents with poor behavioral beliefs on SRH issues had a 37% increased odds of engaging in risky sexual behaviors. Conclusions Therefore, to engage the parents within preventive interventions design to support healthy SRH behaviors among adolescents, the role of authoritative parenting style, and improved quality of parent-adolescent relationship, as well as improving adolescents' behavioral beliefs and parental knowledge towards SRH are essential.